2003
DOI: 10.1139/e03-068
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on New Zealand hot spring sinters: rates of growth and textural development

Abstract: To study the rate of growth of sinters in New Zealand hot springs, field experiments were conducted in seven geothermal areas. At Wairakei, fan-shaped subaqueous deposits of amorphous silica grow rapidly (350 kg a–1 m–2 of drain wall) and are composed of silicified filaments with subordinate bacillus and spirillium-shaped organisms. Characterization of bacteria revealed isolates sharing > 97% 16S rRNA gene sequence homologies affiliated with Thermus, Meiothermus,Bacillus, Tepidomonas, Thermomonas, Porphyrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(152 citation statements)
references
References 38 publications
6
142
0
4
Order By: Relevance
“…Water evaporation is, along with cooling, one of the main abiotic drivers of precipitation and consequently of sinter formation (Walter, 1972(Walter, , 1976a(Walter, , 1976bJones et al, 1998;Braunstein and Lowe, 2001;Mountain et al, 2003;Handley et al, 2005;Schinteie et al, 2007;Tobler et al, 2008). Indeed, in situ studies in which sinter growth on glass slides has been examined (Mountain et al, 2003;Handley et al, 2005Handley et al, , 2008Schinteie et al, 2007;Tobler et al, 2008) have shown that sinter growth occurs mainly above the air-water interface as the result of evaporation of silica-rich water supplied by waves, splashes, or capillary action. Evaporation may also occur rapidly wherever the water level is low and in zones irregularly covered by water, such as around geysers or in irregular or terraced hot spring outflows (Walter, 1972(Walter, , 1976aJones et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water evaporation is, along with cooling, one of the main abiotic drivers of precipitation and consequently of sinter formation (Walter, 1972(Walter, , 1976a(Walter, , 1976bJones et al, 1998;Braunstein and Lowe, 2001;Mountain et al, 2003;Handley et al, 2005;Schinteie et al, 2007;Tobler et al, 2008). Indeed, in situ studies in which sinter growth on glass slides has been examined (Mountain et al, 2003;Handley et al, 2005Handley et al, , 2008Schinteie et al, 2007;Tobler et al, 2008) have shown that sinter growth occurs mainly above the air-water interface as the result of evaporation of silica-rich water supplied by waves, splashes, or capillary action. Evaporation may also occur rapidly wherever the water level is low and in zones irregularly covered by water, such as around geysers or in irregular or terraced hot spring outflows (Walter, 1972(Walter, , 1976aJones et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…By acting as a reactive substratum for passive and heterogeneous silica nucleation, these microorganisms become very rapidly fossilized and eventually encased in the newly formed sinter (Schultze-Lam et al, 1995;Cady and Farmer, 1996;Renaut et al, 1996;Jones et al, 1997Jones et al, , 1998Jones et al, , 2000Jones et al, , 2001Jones et al, , 2003Jones et al, , 2004Jones et al, , 2008Konhauser et al, 2001;Mountain et al, 2003;Kyle et al, 2007;Tobler et al, 2008). The structure of the microbial communities, as well as their daily or seasonal growth variations, thus also contribute to the development of the fabrics and structure of their entombing sinters (Walter et al, 1976;Hinman and Lindstrom, 1996;Konhauser et al, 2001Konhauser et al, , 2004Jones et al, 2005;Berelson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Within this area, the Waiotapu region is characterized by a large number of springs exhibiting elevated arsenic concentrations (Mountain et al 2003). With its 65-meter diameter, the Champagne Pool (CP) represents the largest geothermal feature of Waiotapu with arsenic concentrations ranging from 2.9 to 4.2 mg/L (Hedenquist and Henley 1985).…”
Section: Taupo Volcanic Zone New Zealandmentioning
confidence: 99%
“…Champagne Pool discharges siliceous geothermal fluid rich in arsenic and antimony at approximately 75 u C (Jones et al, 2001). Although a few studies have described microbial activity in Champagne Pool in recent years (Ellis et al, 2005;Jones et al, 2001;Mountain et al, 2003;Phoenix et al, 2005), the successful isolation of a micro-organism has not yet been reported. Previous investigations applying cultureindependent approaches, such as denaturing gradient gel electrophoresis analysis and construction of clone libraries based on the bacterial 16S rRNA gene, have indicated that isolate CP.B2 T , a member of the order Aquificales, is one of the few dominant micro-organisms present in Champagne Pool (Hetzer et al, 2007).…”
mentioning
confidence: 99%